Improving Gross Motor Skill By Traditional Games at Paud Gemilang in Bengkulu - Bendriyanti, Rita Prima; Haryono, Mimpira (Journal of Education Technology, 2021)
This research is motivated by the undevelopment of rough motor of children, children have not been able to perform coordinated body movements to train flexibility, balance, and agility, have not been able to coordinate the movements of the eyes, feet, hands, head in mimicking, have not been able to do physical games with the rules. The purpose of this study is to find out if through traditional game of rope jumping can increase rough motor capacity in group B children in PAUD GEMILANG Bengkulu City. The method used is class action research. The conclusion of this study is that by using traditional game jump rope rough motor skills children can improve. The increase can be seen from the percentage increase after the implementation of actions in cycle I and cycle II. The implementation of the action in cycle I, the percentage of 75% (developed as expected), and the increase occurred significantly indicated in the second cycle with a percentage of 86% (developed very well).